Environmental Impact of Economic Growth: Empirical Evidence from Pakistan - Ditta, Allah; Ayub, Muahammad; Raza, Kashif; Shah, Salyha Zulfiqar Ali (iRASD Journal of Economics, 2021)
Environmental degradation as a consequence of modern technological change is still an unresolved global issue. As countries grow, the cost of this progress has to be born in the form of a rise in carbon emissions. In Pakistan, energy consumption has increased from 34 Million MTOE in 1992 to 98 MTOE in 2019 due to oil and gas-based production. Likewise, the average temperature has risen during the last 50 years in Pakistan. Based on IPAT and Climate change models, this study estimates the two equations model to analyze the impact of economic growth, foreign direct investment, population density and population in urban agglomeration on carbon emissions by using ARDL bound testing methodology. The co-integration relationship was found in both stages with consistency. This study proved the Environmental Kuznets curve (EKC) theory in the case of Pakistan. The more insightful finding is that the large bulge area of the curve between carbon emissions and economic growth highlights that the negative impact of today’s economic growth on the environment will remain for a much longer period in the future. It is also found that carbon emissions are responsible for increasing average temperature resulting in a climatic change in Pakistan. These empirical results indicate that there is a dire need to revisit the growth strategy to achieve sustained economic growth.